The Effect of Service Quality on Satisfaction Outpatient BPJS Patients at the Aid Hospital Kec. Lawang, Malang District, East Java Province in 2023 - Diah Indreswari; Nuraini Nuraini; Ramadhani Syafitri Nasution (PROMOTOR, 2024)
This research establishes a relationship between the quality of hospital services and the satisfaction of BPJS Outpatient patients at the Assisted Hospital in Lawang District, Malang Regency, East Java. Quantitative methods were used in this research, with an analytical survey approach. Data was collected from 126 respondents selected using purposive sampling based on inclusion criteria. The results of univariate analysis show that the majority of respondents have a high school education level and most tend to be dissatisfied with hospital services. Bivariate analysis found a significant relationship between factors such as fitness, responsiveness, empathy, appearance, and service assurance with patient satisfaction.